Multiple Measurements of U.S. Income Inequality - Braun, Denny (The Review of Economics and Statistics, 1988)
Using 1980 state Census data, the Gini ratio, Theil index, coefficient of variation, Atkinson measure (four values), and Nelson index as separate measurements of income inequality are regressed with nineteen SES variables traditionally found significant with Gini in past research. The standard deviation of educational attainment is dominant among all independent variables as the strongest predictor of inequality. Mean family income, dominant in prior research, is a distant second in predictiveness. More diversity than commonality is evident among the nineteen SES variables as they predict income inequality measured by the eight different techniques. Copyright 1988 by MIT Press.